2020
DOI: 10.1088/1757-899x/971/2/022008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the properties of photopolymer prototypes

Abstract: The study of the mechanical properties of photopolymer material SI500. For the manufacture of experimental samples used the method of rapid prototyping stereolithography. The effect of process parameters on tensile and compression strength was studied. It was found that the mechanical strength of the samples is influenced by the layer thickness, exposure time, and additional processing in an ultraviolet chamber. The values of maximum tensile stresses, which are achieved when the layer is exposed for 30 seconds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…See Figure 5(b). These results could confirm earlier results reported by Shumkov et al (2020), who suggested an increase in the exposure time (related to the rise in hatch overcure), improved photopolymer material density SI500 and higher mechanical properties were obtained. In addition, it was shown that the UTS of an SLA part could be increased by either increasing the hatch overcure and/or reducing the layer thickness.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…See Figure 5(b). These results could confirm earlier results reported by Shumkov et al (2020), who suggested an increase in the exposure time (related to the rise in hatch overcure), improved photopolymer material density SI500 and higher mechanical properties were obtained. In addition, it was shown that the UTS of an SLA part could be increased by either increasing the hatch overcure and/or reducing the layer thickness.…”
Section: Resultssupporting
confidence: 92%
“…In a recent study by Seprianto et al (2020), it was concluded that the layer thickness and exposure time (the duration at which the resin is exposed under the light source for each layer) were the most significant factors affecting the impact strength of SLA components. Similar conclusions were reported by Shumkov et al (2020) about the effect of layer thickness and exposure time on the tensile and compressive properties of photopolymer material SI500. Lee et al (2021) also studied the effect of layer thickness on the dimensional accuracy, and the results were in line with Jacob's findings.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation